Blood waters : war, disease and race in the eighteenth-century British Caribbean - Rogers, Nicholas (Studies in early modern cultural, political and social history, 2021)
Far from the romanticised image of the swashbuckling genre of maritime history, the eighteenth-century Caribbean was a 'marchlands' in which violence was a way of life and where solidarities were transitory and highly volatile.